2019
DOI: 10.1158/1535-7163.targ-19-c069
|View full text |Cite
|
Sign up to set email alerts
|

Abstract C069: The identification of MRTX849, a novel KRASG12C inhibitor under clinical investigation, provides insight toward therapeutic susceptibility of KRAS mutant cancers

Abstract: The ability to effectively target mutated KRAS has remained elusive despite decades of research. MRTX849 was identified via structure-based drug design as a potent, selective, and covalent KRASG12C inhibitor that exhibits favorable drug-like properties. MRTX849 is presently under evaluation in clinical trials and its discovery and evaluation is disclosed here for the first time. MRTX849 demonstrated selective modification of the mutant cysteine residue at amino acid residue 12 in GDP-bound KRASG12C and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Similarly, early data from the phase I/II trial of MRTX849 in advanced solid organ KRAS G12C mutant tumours demonstrated an objective response rate (ORR) of 50 % (3/6) in the evaluable patients with NSCLC. [34] In lung cancer, where patients can deteriorate quickly, sequencing of treatments becomes crucial. In our cohort, while 68 % of patients with KRAS G12C mutations received first line systemic therapy, only 35 % and 14 % received second-and third-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, early data from the phase I/II trial of MRTX849 in advanced solid organ KRAS G12C mutant tumours demonstrated an objective response rate (ORR) of 50 % (3/6) in the evaluable patients with NSCLC. [34] In lung cancer, where patients can deteriorate quickly, sequencing of treatments becomes crucial. In our cohort, while 68 % of patients with KRAS G12C mutations received first line systemic therapy, only 35 % and 14 % received second-and third-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As with AMG 510, MRTX849 was found to exhibit a general favorable safety profile. Most adverse events were described as Grade 1 (diarrhea and nausea) 32 . Results from the other KRAS G12C inhibitor, that is, JNJ‐74699157 and LY3499446, do not appear to have been published at this stage.…”
Section: Rasmentioning
confidence: 99%
“…As with AMG 510, MRTX849 was found to exhibit a general favorable safetyprofile. Most adverse events were described as Grade 1 (diarrhea and nausea) 32. Results from the other KRAS G12C inhibitor, that is, JNJ-74699157 and LY3499446, do not appear to have been published at this stage.Although these preliminary results with KRAS G12C inhibitors are promising, it should be stated that overall, KRAS G12C mutations are relatively rare in cancer (12% of KRAS mutations).…”
mentioning
confidence: 98%
“…The clinical data so far suggest a wide therapeutic index for inhibitors like sotorasib and MRTX849. Treatment with these drugs appears well tolerated by most patients, although side effects including diarrhea, anemia, or liver enzyme abnormal-ities have been reported (Christensen et al, 2019;Govindan et al, 2019). It is important to note that unanticipated toxicity in animal or early-phase clinical studies has halted the clinical development of other compounds.…”
Section: Initial Clinical Effectsmentioning
confidence: 99%
“…MRTX849 appears to have similar effects in lung and colorectal cancer patients, but more mature data are needed to validate early results (Christensen et al, 2019). Although similar in inhibitory mechanism, sotorasib and MRTX849 differ in their elimination half-lives (sotorasib, 6 h; MRTX849, 25 h) and administration schemes (with sotorasib dosed daily and MRTX849 twice daily).…”
Section: Initial Clinical Effectsmentioning
confidence: 99%